THU0227 Anca-associated vasculitis: A retrospective study from western india. (23rd January 2014) - Nagaraj, S.; Joshi, P.; Sharma, V.; Buche, A.; Mangat, G.; Samant, R.; Balakrishnan, C.
Abstract : Background: Epidemiological studies on rheumatic diseases in India are few. Vasculitic disorders are under-diagnosed and under-reported. Epidemiological data of AAV is especially scant from western India. 1 Objectives: To describe the clinical profile and outcome of patients with ANCA-associated vasculitis (AAV) from western India. Methods: Demographic profile, clinical features, laboratory data, treatment details, BVAS, EULAR disease stages and therapeutic outcome of patients were analyzed retrospectively. The patients were diagnosed and followed up in the Rheumatology clinic between 2003 and 2011. The patients were classified as per the EULAR guidelines for clinical trials in AAV. 2 Results: A total of 75 patients were studied. 41were females (55%) and 34 were males (45%). Mean age of the patients was 43.4±20.7 years and mean duration of illness 18±16.6 months. The clinical diagnoses were Granulomatosis with polyangiitis (Wegener's) (n=33, 44%), Churg-Strauss Syndrome (n=7, 9%), Microscopic polyangiitis (n=2) and unclassified AAV (n=33, 44%). Systemic involvement: Upper respiratory tract (67%) & lower respiratory tract (60%), skin (44%), kidney (40%), peripheral nerves (40%) and eye (31%). c-ANCA was positive in 41 (53%) and p-ANCA in 34 (47%). 53% had anemia, 59% had leukocytosis and 57% had thrombocytosis. Histopathology (from relevant sites) and imaging studies were obtained in 43 (60%) and 58 (80%) patients respectively. Mean BVAS at presentation was 17.5±7.5. The EULAR disease stage at presentation were: Localised (11%), early systemic (53%), generalised (33%) and severe (3%). Methylprednisolone (70%), cyclophosphamide (60%), methotrexate (25%) and azathioprine (15%) were used for induction. 3 patients underwent plasmapheresis. Maintainence immunosuppressants were prednisolone (96%), cyclophosphamide (39%), azathioprine (33%), methotrexate (28%), and mycophenolate (8%). The mean duration of follow-up was 35.2±20.8 months. 54 (72%) patients achieved remission. Low disease activity was seen in 13 (17%) patients and refractory disease in 8 (11%). Mean duration to achieve remission was 6.7±3.6months. Relapse occurred in 14/54 (26%) patients after a mean duration of 21 months. Death occurred in 3 (4%) patients (pulmonary hemorrhage in 2, MAS in 1). Conclusions: GPA (Wegener's) and Unclassified AAV were the common clinical diagnoses. Early systemic and generalised disease were the commonest EULAR types. Methylprednisolone and cyclophosphamide were the common induction agents while prednisolone and cyclophosphamide were the common maintenance agents. Majority achived remission but relapses were common. References: Joshi VR, G Mittal. Vasculitis–Indian perspective. J Assoc Physicians India 2006;54(Suppl):12–14 Hellmich B, Flossmann O, Gross WL, Bacon P, Willem Cohen-Tervaert J, Guillevin L, et al.EULAR recommendations for conducting clinical studies and/or clinical trials in systemic vasculitis:focus on anti-neutrophil cytoplasm antibody-associated vasculitis. Ann Rheum Dis 2007;66:605–17 Disclosure of Interest: None Declared